A Novel Multi-Tier Architecture Based Mobile Cloud Computing For Enhanced Energy Utilization - Sathesh, A.; Smys, S. (Journal of ISMAC, 2020)
The recent advancements in the mobile devices and the growing needs of the mobile users led to the clubbing of mobile devices with the cloud computing developing a platform coined as mobile cloud computing. The main scope of conceiving this clubbed mobile and cloud paradigm is to direct the tasks that are resource and computationally intensive to the cloud for its execution. While the execution takes place in the cloud, the resources of the mobile users that are clubbed with the cloud remains wasted until the responses are received from the cloud. These results in the excess battery drain causing frequent recharges. To put an end to this, the paper puts forward an the multi-tier architectures in-built with the various level of cluster process for processing to properly handle the mobile device participating in the cloud , minimizing the number of idle mobile users and enhances the energy efficiency. The proposed method is validated using the network simulator-II to evince the energy balancing achieved through the proposed multi-tier architecture based MCC-(mobile cloud computing).